68 A multi-disciplinary approach to delivering PCSK9 inhibitor therapy – first 12 months experience at a specialist cardiothoracic centre. (June 2018) - Hayes, Carol; Browne, Charis; Neves, Emma; Breen, Jane; Priestley-Barnham, Lorraine; Davis, Laura; Pottle, Alison; Thompson, Keith; Manning, Sally; Barbir, Mahmoud
Abstract : Introduction: Following NICE approval of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in June 2016, a multi-disciplinary team (MDT) consisting of nurse specialists in Familial Hypercholesterolaemia, specialist cardiology pharmacists and the lead consultant cardiologist worked together to establish supplementary guidelines and setup a nurse-led PCSK9 clinic to facilitate the initiation and continued monitoring of patients commenced on PCSK9 inhibitors. There are two PCSK9 inhibitors currently approved for use in the UK; evolocumab and alirocumab. Both these drugs are licensed and approved for lowering LDL cholesterol (LDL-C) in selected patients with hypercholesterolaemia. Method: Trust supplementary guidelines were developed in collaboration with the local Clinical Commissioning Group (CCG) which included the referral pathway, criteria for initiation, process for obtaining funding, recommendations for ongoing monitoring and definition of successful response to treatment. A nurse-led PCSK9 clinic was established to manage the initiation and continued monitoring of these patients. Following funding approval, patients attended the clinic for education, training and supervision with their first two injections and further follow-up at 3 months, 6 months (via a telephone appointment) and 12 months. Data was collected prospectively from 7/9/2016 until 30/11/2017 with a minimum of 3 months patient follow-up data. Results: Adverse effects: PCSK9 inhibitors have been generally well tolerated. Four patients (11.1%) have discontinued treatment within the first 6 months due to side effects. Conclusions: The MDT approach to initiating and monitoring PCSK9 therapy has been successful. PCSK9 therapy has been generally well tolerated by patients and a median percentage LDL-C reduction of 49% achieved at 3 months has been maintained at 12 months. Experience to date shows some variation in the response to PCSK9 therapy based on Background lipid lowering therapy.